Conservation of amino acids in multiple alignments: aspartic acid has unexpected conservation - Fiser, A; Simon, I; Barton, G (Elsevier, 1996)
Analysis of the relationship between surface accessibility and amino acid conservation in multiple sequence alignments of homologous proteins confirms expected trends for hydrophobic amino acids, but reveals an unexpected difference between the conservation of Asp, Glu and Gln. Even when not in an active site, Asp is more highly conserved than Glu. There is a clear preference for conserved and buried Asp to be present in coil, but there is no tendency for Asp to conserve φ/ψ in the ++ region of the Ramachandran map. Glu does not show any preference to be conserved in a particular secondary structure. Analysis of recently derived substitution matrices (e.g. BLOSUM) confirms that Glu tends to substitute more frequently with other amino acids than does Asp. Analysis of relative accessibility versus relative conservation for individual amino acid positions in alignments shows a negative correlation for all amino acid types. With the exception of Arg, Lys, Gly, Glu, Asp and Tyr, a relative conservation of > 2 suggests the amino acid will have a relative accessibility of < 50%. Observation of conserved Cys, Gly or Asp in a reliable multiple aligmnent suggests a position important for the structure of the protein. Furthermore, the Asp is likely to be involved in polar interactions through its side chain oxygen atoms. In contrast, Gln is the least conserved amino acid overall.